JANICKIEGO MIŁOŚĆ OJCZYZNY I JEGO POEZJA PATRIOTYCZNA. WSPOMNIENIE W 500-LECIE URODZ IN POETY - Lewandowski, Ignacy (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2017)
The paper aims to present some aspects of Janicki’s poetry devoted to various existence problems of those times, i. e. the social poor, education opportunities for them, and insisting on the nobility taking greater care of the country.